2014
DOI: 10.1017/s1368980014000986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a simple educational intervention in well-baby clinics on women’s knowledge about and intake of folic acid supplements in the periconceptional period: a controlled trial

Abstract: Objective: To test the hypothesis that a concise intervention to promote the preconception use of folic acid (FA) supplements among mothers who visit a wellbaby clinic (WBC) for the 6-month check-up of their youngest child is effective. Effectiveness was measured as intention to use or actual use of FA supplements before a next pregnancy among women who expected to be pregnant within 0-12 months. Design: Controlled intervention study with independent samples of intervention and control mothers. The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This potential role for PCHC services in delivering interconception care has been recognized in a Dutch governmental advisory report on preconception care [8]. In addition, two recent studies acknowledged this opportunity and aimed at reaching women for advice on interconception care in well-baby clinics [2, 19]. Nevertheless, interconception care has not become standard care within PCHC services.…”
Section: Introductionmentioning
confidence: 99%
“…This potential role for PCHC services in delivering interconception care has been recognized in a Dutch governmental advisory report on preconception care [8]. In addition, two recent studies acknowledged this opportunity and aimed at reaching women for advice on interconception care in well-baby clinics [2, 19]. Nevertheless, interconception care has not become standard care within PCHC services.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have specifically assessed the effectiveness of an ICC intervention on improved pregnancy outcomes or proxy outcomes such as behavior change (see Supplementary addendum table) [17]. Only two studies have shown a positive impact; suggesting improved folic acid use and suggesting increased pregnancy intervals and less adverse outcomes in a high-risk population [18,19]. Many ICC programs have been described without reporting on effectiveness or only providing feasibility and process evaluations [20][21][22][23][24][25][26][27][28].…”
Section: Literaturementioning
confidence: 99%
“…In the Netherlands, a single visit around 6 weeks postpartum is recommended, but Lu et al have recommended expanding the number of visits to apply ICC [3]. The role of maternity care providers in postpartum care and ICC has been described [11,73,74], but also other healthcare providers have been suggested to take part in ICC such a pediatric care providers [19,23,75,76], internists [61], sexually transmitted disease clinics [77], general practitioners and genetic counselors [78]. Actually, every office visit is an opportunity for ICC [9].…”
Section: Literaturementioning
confidence: 99%
“…In the Netherlands, individual counselling can be provided through general practices, municipal health services, or midwives and gynaecologists [ 8 ]. Preconception care has shown to be effective in improving maternal health behaviour, such as folic acid use, smoking and alcohol cessation, diabetic control and obesity prevention before pregnancy, and preventing congenital disorders [ 12 15 ]. Women with a lower socioeconomic background are at greatest risk of complications during and after pregnancy, yet they are least likely to participate in preconception screening, risk assessment and counselling [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%